Quantifying Iron Oxide Mineral Contents in Miocene Oceanic Red Beds for the Deep-Sea Oxidation Evolution in the South China Sea - Lyu, Xuan; Liu, Zhifei; Wu, Qiong; Colin, Christophe; Yu, Xun; Liu, Chuanlian; Li, Qianyu (Frontiers in Earth Science, 2022)
International Ocean Discovery Program (IODP) Expedition 349 recovered Miocene oceanic red beds overlying the basaltic basement in the South China Sea. The occurrence of oceanic red beds provides an opportunity to understand the deep-sea redox conditions when the South China Sea was open to the western Pacific during the Miocene. Here, we investigated iron oxide mineral contents along with major element compositions of the oceanic red beds at Site U1433 to reveal the Miocene deep-sea oxidation environment of the South China Sea and its interaction with the western Pacific. The results show that these samples contain 0.20–1.48% hematite (average 0.50%) and 0.30–2.98% goethite (average 1.20%). Their contents have good linear correlations with color reflectance a* (red) and b* (yellow), respectively, implying that the reddish-brown color of the Miocene oceanic red beds was resulted from a mixture of hematite and goethite. Compared to other oceanic red beds worldwide, the occurrence of hematite and goethite in the South China Sea is considered to form under an oxic bottom water environment with extremely low sedimentation rate. The (hematite + goethite)/(100 – Al2O3) ratio is adopted to reconstruct the evolution of bottom water oxidation during the early-middle Miocene. A continuously decreased oxidation trend from 18.4 to 11.6 Ma, along with two strengthened oxidation events occurring at around 15 Ma and 14 Ma, is observed to dominate the environment evolution of the abyssal South China Sea. We infer that this long-term decreased oxidation trend was caused by the gradual blocking of oxygen-rich bottom water from the western Pacific since the early Miocene, while the two oxidation events were likely attributed to the rapid thermal subsidence of the South China Sea and the global cooling during the middle Miocene Climate Transition, respectively.